Postpartum computed tomography angiography of the fetoplacental macrovasculature in normal pregnancies and in those complicated by fetal growth restriction. (23rd February 2018) - Thunbo, Mette Ø.; Sinding, Marianne; Korsager, Anne S.; Frøkjær, Jens B.; Østergaard, Lasse R.; Petersen, Astrid; Overgaard, Charlotte; Sørensen, Anne
Abstract: Introduction: Current knowledge of the fetoplacental vasculature in fetal growth restriction (FGR) due to placental dysfunction focuses on the microvasculature rather than the macrovasculature. The aim of this study was to investigate the feasibility of computed tomography angiography to analyze the fetoplacental macrovasculature in normal and FGR pregnancies. Material and methods: We included 29 placentas (22–42 weeks of gestation) from normal birthweight pregnancies and eight placentas (26–37 weeks of gestation) from FGR pregnancies (birthweight < −15% and abnormal umbilical Doppler flow). We performed postpartum placental computed tomography angiography followed by semi‐automatic three‐dimensional image segmentation. Results: A median of nine (range seven to eleven) vessel generations was identified. In normal birthweight placentas, gestational age was positively linearly correlated with macrovascular volume ( p  = 0.002), vascular surface area ( p  < 0.0005) and number of vessel junctions ( p  = 0.012), but not with vessel diameter and inter‐branch length. The FGR placentas had a lower weight ( p  = 0.004) and smaller convex volume ( p  = 0.022) (smallest convex volume containing the macrovasculature); however, macrovascular volume was not significantly reduced. Hence, macrovascular density given as macrovascular outcomes per placental volume was increased in FGR placentas: macrovascular volume per convex volume ( p  = 0.004), vascular surface area per convex volume ( p  = 0.004) and number of vessel junctions per convex volume ( p  = 0.037). Conclusions: Evaluation of the fetoplacental macrovasculature is feasible with computed tomography angiography. In normal birthweight placentas, macrovascular volume and surface area increase as pregnancy advances by vessel branching rather than increased vessel diameter and elongation. The FGR placenta was smaller; however, the macrovascular volume was within normal range because of an increased macrovascular density.